Laryngeal Chondroma: A Rare Diagnosis in This Localization - Ebru Tastekin; Semsi Altaner; Cem Uzun; Ahmet R. Karasalihoglu; Cigdem Ozdemir; Ali Kemal Kutlu (Case Reports in Pathology)
Primary chondroid tumors of the larynx represent less than 1% of all laryngeal tumors. Most of them are chondromas and they often involve to the cricoid cartilage. A 31-year-old male patient applied to the oto-laryngology service with a history of dysphonia and dyspnea. Microlaryngoscopy revealed 2 cm sized, ill-defined, covered with regular mucosa, porous, and hard mass on posterior surface of crycoid cartilage in subglottic area. Following the excision of the lesion, histopathologic examination revealed as chondroma. Two years later, local recurrence was detected and the diagnosis was again chondroma. There was no complaint of the patient in last 3 and half years of follow-up. Chondroma should carefully be differentiated from chondrosarcoma and the patients should be followed for possible recurrences.